Effectiveness of a community-integrated intermediary care (CIIC) service model to enhance family-based long-term care for Thai older adults in Chiang Mai, Thailand: a cluster-randomized controlled trial TCTR20190412004 - Myo Nyein Aung; Saiyud Moolphate; Thin Nyein Nyein Aung; Yuka Koyanagi; Akrapon Kurusattra; Sutatip Chantaraksa; Siripen Supakankunti; Motoyuki Yuasa (BMC, 2022)
Abstract Background Populations around the world are ageing faster, with the majority living in low- and middle-income countries where health and social care are yet to be universal and inclusive for the ageing population. This community-integrated intermediary care (CIIC) model is a novel prevention-based, long-term care model enhancing the family-based care system traditionally practised in Thailand and neighbouring Asian countries, and many low-and middle-income countries globally. This study assessed the effectiveness of the CIIC model in Chiang Mai, Thailand. Methods The two-arm parallel intervention study was designed as a cluster-randomized controlled trial. The study population at randomization and analysis was 2788 participants: 1509 in six intervention clusters and 1279 in six control clusters. The research protocol was approved by the WHO Research Ethics Review Committee (WHO/ERC ID; ERC.0003064). The CIIC service intervention model is a combination of formal care and informal care in a subdistrict setting consisting of three components: (1) care prevention delivered as community group exercise and home exercise; (2) care capacity-building of the family caregiver; and (3) community respite service. The primary outcome was family caregivers' burden at 6-month follow-up, and secondary outcome was activities of daily living. Analysis applied the intention-to-treat approach using cluster-level analysis via STATA 16 SE. Results Baseline characteristics did not differ between the two arms. Loss of follow up was 3.7%. Mean age of the participants was 69.53 years. Women constituted 60%. The COVID-19 pandemic caused delayed implementation. The proportion of families with reduced caregiver burden at 6-month follow-up was higher among the intervention clusters (mean 39.4%) than control clusters (mean 28.62%). The intervention clusters experienced less functional decline and fewer people with depression. Conclusions When communities are integrated for preventing care, and families are empowered for giving care, it is possible to secure universal access to health and social care for the older persons, with basic resources mobilized from communities. This study had shown the CIIC model as an effective and potential step to the realization of universal health and long-term care coverage being inclusive of ageing populations in Thailand and globally. Trial registration: This trial was registered at the Thailand Clinical Trial Registry-Trial registration number TCTR20190412004, https://www.thaiclinicaltrials.org/#